From Here to Nirvana: The Yoga Journal Guide to Spiritual India - Anne Cushman: Jerry Jones; CUSHMAN (Anne): JONES (Jerry) (New York Riverhead Books, 1998)
From yogis to ashrams to temples, an in-depth travel guide to the spiritually significant sites of India provides detailed directions and contacts, information on food, facilities, tips on what to bring, photographs and maps, local lore, and much more.
Keywords: Religion; Ashramas; Religious Institution; India